Investigação das alterações locais e sistêmicas do onset da osteoartrite em joelhos de ratos após a transecção do ligamento cruzado anterior - Dias, Carolina Náglio Kalil (Universidade Federal de São Carlos, 2012)
Objective: To evaluate the chondrocytes apoptosis by caspase 3 expression and its relation with the knee articular cartilage thickness and cellularity, at the acute phase after anterior cruciate ligament (ACL) transection, as the experimental model of osteoarthritis (OA). Material and Methods: Seventy two male Wistars rats were divided into 3 groups: ACL transection group (ACLT); control group (C); and sham group (S). Each group was subdivided into 4 subgroups: 24h, 48h, 72h and 1 week, according to the period following the procedures performed. The medial condiles of the left knees were processed in paraffin and stained with HE for cartilage thickness and cellularity analysis, by morphometry. Caspase 3 expression was evaluated through immunohistochemical method. Statistical analysis was performed by using the Kolmogorov-Smirnov test to assess the normality of the data, and then ANOVA with post hoc Duncan. Results: There was no statistical difference for articular cartilage thickness and cellularity between the groups. Regarding the caspase 3 expression, the C had smaller expression than the other groups. The ACLT 24h and ACLT 48h groups had increased expression of caspase-3 than their respective C and S. The ACLT 72h was not different from S 72h, and presented a lower caspase 3 expression compared to the other groups. The ACLT 7days and S 7days groups had higher expression than any other group. Conclusion: The chondrocyte apoptosis present since the OA beginning, using the ACL transection model of OA, however the articular cartilage thickness and cellularity changes can be modified at a later stage.
Keywords: Fisioterapia; Osteoartrite; Ligamento cruzado anterior; Apoptose; Citocina; Cartilagem articular; Articular cartilage; Osteoarthritis; Anterior Cruciate Ligament; Chondrocyte; Apoptosis; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL